Professional learning and development of two groups of pre-service teachers with different scientific knowledge bases and different teaching training in the course of their studies. (June 2019) - Rozenszajn, Ronit; Snapir, Zohar; Machluf, Yossy
Highlights: Pre-service teachers (PST) demonstrated different patterns of professional learning. PST with in-depth CK were concerned with inquiry teaching strategies. PST with in-depth CK were concerned with high-order thinking skills strategies. PST with more teaching experience were challenged by the student-centered strategy. Abstract: This research study evaluated the professional development of two groups of pre-service biology teachers during a year-long biology didactics course in two different academic institutions. Verbal and qualitative analyses of lesson transcripts were employed to characterize explicit knowledge, while content and cluster analyses of the repertory grid technique were employed to characterize tacit knowledge. The group of pre-service teachers with lower content knowledge (CK) and more teaching experience during their training was concerned with student- and teacher-centered practices. The group with higher CK and less teaching experience was concerned with high-order thinking skills and the knowledge gap between themselves and their students. Therefore, we recommend: (1) engaging pre-service teachers with low CK in inquiry experiences, which may foster high-order thinking skills in their practice; (2) all pre-service teachers, regardless of their CK, should practice substantial teaching while studying, which may bridge the knowledge gap between themselves and their students.